Addressing Consumerism and the Planetary Health Crisis: Behavioral Economics Approach in Public Policy - Sarkar, Atanu (Frontiers in Energy Research, 2022)
Our pervasive sense of dissatisfaction has become an addiction, and it is driving us to have an unstoppable longing for materialistic things, resulting in anthropogenic disruptions of the earth's natural systems and their catastrophic consequences. Behavioral economics integrates insights from psychological research into economic science. The policy brief explores how behavioral economics can be a practical approach for citizens to adopt pro-environmental behavior. It is worth examining why some people do not embrace green options, despite knowing their positive environmental impacts. Human decision anomalies are often driven by intuitively available simplification, making the decision by mental shortcut to achieve, known as a heuristic. Nudging people and setting up a choice architecture can be better ways to alter peoples’ behavior to adopt a pro-environment lifestyle.